FAKTOR PENDORONG MASYARAKAT DESA PENINSUNG DALAM MENJAGA HUTAN ADAT DI KECAMATAN SEPAUK - Melia, Anasia; Zainal, Sofyan; Idham, Muhammad (JURNAL HUTAN LESTARI, 2016)
The increase of the population and a wide range of activities can provide a great influence towards the utilization of the natural resources that come from the forest. This has resulted in reduced customs and forest area of occurrence is increasingly threatened. This will require good of indigenous forest management, so it can retain and sustainment the forest. The problem is the factors are a driving factor in maintaining indigenous forest of society and if there are relation between the individual factors that led to the existence of the indigenous forest to be good or not. This research is aim to know the driving factor in maintaining indigenous forest of society and to know the relation of each the individual factorsis: the income rate, level of public knowledge, customary law, and public perception in maintaining indigenous forest. This research used a descriptive survey and interview techniques. Result of this research the driving factor of society in maintaining indigenous forest in the village of Peninsung because forests retain and store where the water source that river in the village are not easy to dry be used by communities to used daily as well forest products is are plentiful, especially timber and non timber that can be utilized by the public. Keywords: Driving factor, villagers, indigenous forest